Online Learning and Residents' Acquisition of Mechanical Ventilation Knowledge: Sequencing Matters. Issue 1 (January 2020) - Wolbrink, Traci A.; van Schaik, Sandrijn M.; Turner, David A.; Staffa, Steven J.; Keller, Eleanor; Boyer, Donald L.; Chong, Grace; Cross, Jarrod; del Castillo, Sylvia; Feng, Andrew; Hum, R. Stanley; Jacob James, Ebor; et al.
Abstract : Objective: Rapid advancements in medicine and changing standards in medical education require new, efficient educational strategies. We investigated whether an online intervention could increase residents' knowledge and improve knowledge retention in mechanical ventilation when compared with a clinical rotation and whether the timing of intervention had an impact on overall knowledge gains. Design: A prospective, interventional crossover study conducted from October 2015 to December 2017. Setting: Multicenter study conducted in 33 PICUs across eight countries. Subjects: Pediatric categorical residents rotating through the PICU for the first time. We allocated 483 residents into two arms based on rotation date to use an online intervention either before or after the clinical rotation. Interventions: Residents completed an online virtual mechanical ventilation simulator either before or after a 1-month clinical rotation with a 2-month period between interventions. Measurements and Main Results: Performance on case-based, multiple-choice question tests before and after each intervention was used to quantify knowledge gains and knowledge retention. Initial knowledge gains in residents who completed the online intervention (average knowledge gain, 6.9%; SD, 18.2) were noninferior compared with those who completed 1 month of a clinical rotation (average knowledge gain, 6.1%; SD, 18.9; difference, 0.8%; 95% CI, –5.05 to 6.47; p = 0.81). Knowledge retention was greater following completion of the online intervention when compared with the clinical rotation when controlling for time (difference, 7.6%; 95% CI, 0.7–14.5; p = 0.03). When the online intervention was sequenced before (average knowledge gain, 14.6%; SD, 15.4) rather than after (average knowledge gain, 7.0%; SD, 19.1) the clinical rotation, residents had superior overall knowledge acquisition (difference, 7.6%; 95% CI, 2.01–12.97; p = 0.008). Conclusions: Incorporating an interactive online educational intervention prior to a clinical rotation may offer a strategy to prime learners for the upcoming rotation, augmenting clinical learning in graduate medical education. Abstract : Supplemental Digital Content is available in the text.